2010
DOI: 10.1261/rna.2194910
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and targetome analysis in MIR155 expressing cells using RNA-seq

Abstract: Previous studies have demonstrated the utility of microarray expression analysis to identify potential microRNA targets. Nevertheless, technical limitations intrinsic to this platform constrain its ability to fully exploit the potential of assessing transcript level changes to explore microRNA targetomes. High-throughput multiplexed Illumina-based next-generation sequencing (NGS) provides a digital readout of absolute transcript levels and imparts a higher level of accuracy and dynamic range than microarray pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 40 publications
(56 reference statements)
3
62
0
Order By: Relevance
“…The expression profile of ZNF652 in these cell lines resembles an inverse reflection of their miR-155 expression profiles, which is consistent with previous reports demonstrating that miR-155 targets the ZNF652 transcript through a specific seed sequence in the 3'UTR (19,20). Indeed, over-expression of miR-155 markedly reduced endogenous ZNF652 protein levels in the H1299 epithelial lung carcinoma cell line ( Figure 4C …”
Section: Znf652 Is An Epithelial Marker and Suppresses Tumor Cell Invsupporting
confidence: 90%
“…The expression profile of ZNF652 in these cell lines resembles an inverse reflection of their miR-155 expression profiles, which is consistent with previous reports demonstrating that miR-155 targets the ZNF652 transcript through a specific seed sequence in the 3'UTR (19,20). Indeed, over-expression of miR-155 markedly reduced endogenous ZNF652 protein levels in the H1299 epithelial lung carcinoma cell line ( Figure 4C …”
Section: Znf652 Is An Epithelial Marker and Suppresses Tumor Cell Invsupporting
confidence: 90%
“…miR-155 target mRNAs are implicated in hematopoietic development and disease (39), transcription regulation (31), the NK-B signaling pathway (32), B-cell proliferation, and lymphocyte homeostasis (40). Recent genome-wide high-throughput studies, such as mRNA sequencing (mRNA-seq) analyses, stable isotope labeling by amino acids in cell culture (SILAC) proteomics, and HITS-CLIP, have confirmed some of these targets, as well as identified additional ones (40)(41)(42). In EBV-positive lymphoblastoid cell lines (LCLs) and diffuse large B-cell lymphomas (DLBCLs), inhibition or deletion of miR-155 reduces growth and promotes apoptosis (33).…”
Section: The Boostermentioning
confidence: 99%
“…A total of 103 target genes (including 11 target genes validated in other studies) were identified in a single high-throughput next-generation sequencing study and validated by luciferase reporter assay (50). The remaining 44 target genes and their method of validation are displayed in Supplementary Table S2.…”
Section: Target Genes Of Mir-155mentioning
confidence: 99%